EFEKTIVITAS EKSTRAK ETANOL DAUN BINAHONG (Anredera cordifolia Steen.) SEBAGAI ANTIDIABETES PADA MENCIT (Mus muculus. L) - Stevani, Anggita Nadia; Rissa, Mexsi Mutia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Diabetes Mellitus is a disease with lifelong treatment, while antidiabetic drugs consumed can cause side effects in the long term, so it requires alternative therapies with traditional medicinal plants such as the binahong plant (Anredera cordifolia (Ten) Steen.) which contains flavonoids and saponins. These compounds have the ability to lower blood sugar levels. This study aims to determine the antidiabetic effect of the ethanol extract of binahong leaves on alloxan-induced swiss male males. This type of research was experimental with the method of pre and post test with controlled group design, using 15 male swiss strains which were divided into 3 groups. Negative control (CMC Na 0.5%), positive control (Glibenclamide dose 0.65 mg/KgBB), and the treatment group ethanol extract of binahong leaves dose 17.5 mg/KgBB. Data on blood sugar levels obtained were analyzed using SPSS 23 with a 95% confidence level. The results of this study showed that the ethanol extract of binahong leaves at a dose of 17.5 mg/kg could reduce blood sugar levels in alloxan-induced swiss male mice. Data on decreasing blood sugar levels obtained were analyzed by One Way ANOVA, followed by LSD. The test results showed that the decrease in blood sugar levels in mice given the ethanol extract of binahong leaves at a dose of 17.5 mg/KgBW was not significantly different from that given by glibenclamide at a dose of 0.65 mg/KgBW (sig > 0.05).